DESIGN AND CONSTRUCTION OF VERTICAL HELIX SAVONIUS WIND TURBINE FOR PUBLIC STREET LIGHTING - Sagita Rochman; Krishna Wijayakusuma; Rivaldo Josua Jetrin Rolos (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2022)
Wind power generator for lighting public roads in Tambakrejo Village, Sumbermanjing District, Malang Regency in order to minimize the level of traffic accidents. This power plant utilizes wind resources that blow to drive a wind turbine generator that will produce electrical energy. The use of wind to become electrical energy is designed from a vertical helix savonius type wind turbine as a medium for receiving wind gusts that will drive a generator to create electrical energy. The advantage of this helix savonius wind turbine can accommodate all cardinal directions because it has 2 blades that rotate 180. The role of the battery is to store electrical energy before it is distributed for public street lighting. Wind turbines or wind power plants are one of the renewable energy sources that are environmentally friendly and are starting to be widely developed at this time. In the storage and use of this electrical energy, it is very necessary to pay attention so that there is no overcharging / overcharge and excess usage / overdischarge. Therefore, the charge controller battery charging setting is used which will regulate charging or discharging. From the battery it will be connected to the Photocell for automatic control when it is dark and the light will turn on.